2013
DOI: 10.1007/s00280-013-2121-1
|View full text |Cite
|
Sign up to set email alerts
|

PI3K and MEK inhibitor combinations: examining the evidence in selected tumor types

Abstract: The PI3K/AKT/mTOR and RAS/RAF/MEK/ERK pathways are two of the most frequently dysregulated kinase cascades in human cancer. Molecular alterations in these pathways are implicated in tumorigenesis and resistance to anticancer therapies. The PI3K/AKT/mTOR and RAS/RAF/MEK/ERK pathways are known to interact with each other at several nodes, and mounting evidence suggests that dual blockade of both pathways may be required to achieve anticancer effects in certain contexts. This may include tumor types with a high f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
168
3
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(177 citation statements)
references
References 99 publications
2
168
3
4
Order By: Relevance
“…The combined treatment with cetuximab plus regorafenib shows a synergistic antitumor effect both in vitro and in vivo, providing the rational for the clinical development of this combination. These results are consistent with previous reports, which showed that combined inhibition of different growth controlling pathways might potentially exhibit a better therapeutic efficacy compared with inhibition of a single pathway (38)(39)(40). In this respect, regorafenib inhibits multiple cell membrane tyrosine kinase receptors that are involved in key processes of cancer development and progression, including angiogenesis (17).…”
Section: Discussionsupporting
confidence: 83%
“…The combined treatment with cetuximab plus regorafenib shows a synergistic antitumor effect both in vitro and in vivo, providing the rational for the clinical development of this combination. These results are consistent with previous reports, which showed that combined inhibition of different growth controlling pathways might potentially exhibit a better therapeutic efficacy compared with inhibition of a single pathway (38)(39)(40). In this respect, regorafenib inhibits multiple cell membrane tyrosine kinase receptors that are involved in key processes of cancer development and progression, including angiogenesis (17).…”
Section: Discussionsupporting
confidence: 83%
“…genetic changes in these receptors or the mutational activation of RAS or RAF are rare, these tumors often harbor other genetic alterations that promote RAS-ERK pathway activity (26)(27)(28)(29)(30)(31). Supporting the importance of this signaling, TNBC cells are particularly sensitive to drugs such as MEK or PI 3-kinase inhibitors, and combination therapies have been analyzed in clinical trials (23,24,78,79).…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function mutations in PTEN, which is a tumor suppressor and an antagonist of the PI3K/AKT pathway, induce AKT-regulated metastasis in CRCs 54 . The MEK/ERK and PI3K/AKT pathways often converge to activate a cap-dependent translation through survivin knockdown, which can inhibit metastasis 55 . Therefore, targeting both pathways together is more clinically effective 56 .…”
Section: Mutational Landscape In Chromosomal Instabilitymentioning
confidence: 99%